Multicultural Psychological Empowerment Scale for Saudi Women - Moubarak, Hanaa Faize A.; Afthanorhan, Asyraf; Alrasheedi, Eisa Sneitan N. (Frontiers in Psychology, 2022)
The current study aimed to construct a multicultural psychological empowerment scale for Saudi women depending on the four dimensions of psychological empowerment; meaningfulness, impact, self-efficacy, and self-determination. It was applied to a sample (1080) of Saudi women from various age categories, different social, educational and employment status and geographical regions. Pooled Confirmatory Factor Analysis (PCFA) was using to determine the reliability and validity of the scale. As a results, the reliability and validity of the entire model was satisfied. Specifically, the composite reliability values were fall in the range between 0.804 and 0.883. Meanwhile, the convergent validity was achieved as these values produced from each construct were higher than the acceptable limit of 0.50. Also, the construct validity of fitness indexes (CFI, IFI TLI, RMSEA, and Chisq/Df) was achieved. In its final form, MPES-SW included (26) phrases distributed over its four dimensions. The study suggested systematic measurements of psychological empowerment for Saudi women from different categories, targeted with therapeutic, preventative and developmental visions, plans and programs to determine the extent of their psychological empowerment.